Impact of disconnected pancreatic duct syndrome on endoscopic ultrasound-guided drainage of pancreatic fluid collections - Wang, Lillian; Elhanafi, Sherif; Storm, Andrew C.; Topazian, Mark D.; Majumder, Shounak; Abu Dayyeh, Barham K.; Levy, Michael J.; Petersen, Bret T.; Martin, John A.; Chari, Suresh T.; Vege, Santhi S.; Chandrasekhara, Vinay (Endoscopy, 2020)
Background Endoscopic intervention for pancreatic fluid collections (PFCs) with disconnected pancreatic duct syndrome (DPDS) has been associated with failures and increased need for additional endoscopic and non-endoscopic interventions. The primary aim of this study was to determine the outcomes of endoscopic ultrasound (EUS)-guided transmural drainage of PFCs in patients with DPDS.Methods In patients undergoing EUS-guided drainage of PFCs from January 2013 to January 2018, demographic profiles, procedural indications and details, adverse events, outcomes, and subsequent interventions were retrospectively collected. Overall treatment success was determined by PFC resolution on follow-up imaging or stent removal without recurrence.Results EUS-guided drainage of PFCs was performed in 141 patients. DPDS was present in 57 of them (40 %) and walled-off necrosis was the most frequent type of PFC (55 %). DPDS was not associated with lower clinical success, increased number of repeat interventions, or increased time to PFC resolution. Patients with DPDS were more likely to be treated with permanent transmural plastic double-pigtail stents (odds ratio [OR] 6.4; 95 % confidence interval [CI] 2.5 – 16.5; P < 0.001). However, when stents were removed, DPDS was associated with increased PFC recurrence after stent removal (OR 8.0; 95 %CI 1.2 – 381.8; P = 0.04).Conclusions DPDS frequently occurs in patients with PFCs but does not negatively impact successful resolution. DPDS is associated with increased PFC recurrence after stent removal.